BS EN 13126-3. Building hardware. Hardware for windows and door- height windows. Requirements and test methods. Part 3. Handles, primarily for Tilt&Turn, Tilt-First and Turn-Only hardware (26th August 2021) - British Standards Institution
No abstract available